Internet of things: implementasi dalam perpustakaan - Kurniawan, Lucky; Firdaus, Ovandio Iqbal (2018)
InternetofThingmerupakansebuahjaringanyangmenghubungkanberbagaiobjekdanmemilikiidentitaspengenaldanalamatIPsehinggadapatsalingbertukarkomunikasidaninformasimengenaidirinyamaupunligkungandisekitarnya.ObjekdalamIoTdapatmenggunakanmaupunmenghasilkanlayananlayanandansalingbekerjasamauntukmencapaisuatutujuanBersama.DengankemampuaniniIoTdapatdiartikaninternetsebagaikomputasidimanasajakapanjasadanbagaimanasajamenjadiapasajasiapasajadanlayananapasaja.DanadabeberapaisuyangmenjaditantangandalampengimplementasianIoTdiperpustakaanadalahtergantikannyapustakawandenganrobotsafetysecuritydanbiayayangmahal.KatakunciInternetofThings(IoT)perpustakaan.